Kazimierz Łaski's Lectures in Macroeconomics under financial capitalism - Jerzy Osiatyński (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2019)
The paper summarizes the discussion among Łaski's inner circle regarding the relevance of Kaleckian treatment of money under financial capitalism. The context of that debate was the project of a joint textbook in macroeconomics, the building blocks of which would be Kalecki's theory, and which would take into account the present-day financialization. With Łaski's death the opportunity of doing the project was gone. Of the two closely interlinked questions under debate, the first dealt with permissible simplifications regarding determinants of money supply and interest rates, and the second with how to extend Kaleckian theory to link the real economy sector more tightly with its financial sector. The paper argues that for an introductory textbook in macroeconomics Kalecki's and Łaski's simplifications are legitimate. On the second issue the paper finds the introduction of two financial subsectors and the discussion of their interlinks with the real economy sector to be an important and possible way of investigating macroeconomic crises and instability within the Kaleckian macroeconomic framework. Another way would be the expansion and modification of Kalecki's investment decision function, which would continue to generate an automatic business cycle due to changes in fixed capital investment but also in combination with factors determining financial investment.
Keywords: E11; E12; E32; E44; 330; Michał Kalecki; Kazimierz Łaski; financial capitalism; business cycle; money and interest